The Interaction of EphA4 With PDGFRβ Regulates Proliferation and Neuronal Differentiation of Neural Progenitor Cells in vitro and Promotes Neurogenesis in vivo - Chen, Qingfa; Song, Hao; Liu, Chuanguo; Xu, Jun; Wei, Chuanfei; Wang, Wei; Han, Fabin (Frontiers in Aging Neuroscience, 2020)
Neural progenitor cells (NPCs) have great potentials in cell replacement therapy for neurodegenerative diseases, such as Alzheimer disease (AD) by promoting neurogenesis associated with hippocampal memory improvement. Ephrin receptors and angiogenic growth factor receptors have a marked impact on the proliferation and differentiation of NPCs. Although EphA4 was shown to directly interact with PDGFRβ, the functional effects of this interaction on neurogenesis in cultured NPCs and adult hippocampus have not yet been studied. Immunoprecipitation demonstrated that EphA4 directly interacted with PDGFRβ in NPCs under ligand stimulation. Ephrin-A1 and PDGF-BB significantly increased proliferation and neuronal differentiation of NPCs, which was further augmented by combined treatment of Ephrin-A1 and PDGF-BB. We also found that ligand-dependent proliferation and neuronal differentiation were inhibited by the dominant-negative EphA4 mutant or a PDGFR inhibitor. Most importantly, injection of ephrin-A1 and/or PDGF-BB promoted hippocampal NPC proliferation in the APP/PS1 mouse model of AD, indicating direct interaction of EphA4 with PDGFRβ plays a functional role on neurogenesis in vivo. Finally, studies in NPCs showed that the EphA4/PDGFRβ/FGFR1/FRS2α complex formed by ligand stimulation is involved in neurogenesis via ERK signaling. The present findings provided a novel insight into the functional role of direct interaction of EphA4 and PDGFRβ in neurogenesis, implicating its potential use for treating neurodegenerative diseases.